Design and validation of a questionnaire to measure principal management and quality in educational services - Buendía Giribaldi , Atilio Rodolfo (2022)
The objective of the study was to design and validate a questionnaire that measures the director's management and the quality of educational services. A validation study of a questionnaire that allows measuring the director's management and the quality of educational services was carried out. The population consisted of 75 fifth-year high school students from the Albert Einstein scientific college, enrolled in 2019, the sample obtained after applying the formula for finite samples was 45 students. The questionnaire was designed by the researcher, which was based on scientific studies, it consisted of two parts, one aimed at measuring the director's management, which consisted of 4 dimensions: institutional, pedagogical, administrative and community management, with a total of 24 questions. The validity of the questionnaire was verified through 3 experts where the correlation was submitted, resulting in a p value of less than 0.05 and reliability was obtained through Conbrash's alpha with a value of less than 0.07 in all dimensions. Therefore, it is concluded that the questionnaire used is reliable.